Pulsed Electrical Stimulation of the Human Eye Enhances Retinal Vessel Reaction to Flickering Light - Freitag, Stefanie; Hunold, Alexander; Klemm, Matthias; Klee, Sascha; Link, Dietmar; Nagel, Edgar; Haueisen, Jens (Frontiers in Human Neuroscience, 2019)
Recent studies indicate therapeutic benefits of electrical stimulation in cases of specific ophthalmic diseases that are associated with dysfunctional ocular microcirculation. This suggests effects of electrical stimulation on vascular functions. In the present study, we investigated the effects of electrical stimulation on retinal vessel reactions using dynamic vessel analysis (DVA). Eighty healthy subjects were randomly assigned to one of three groups receiving electrical stimulation with different current intensities: 400 µA (n = 26); 800 µA (n = 27); 1200 µA (n = 27). The electrode montage for electrical stimulation consisted of a ring-shaped active electrode surrounding one eye and a square return electrode at the occiput. Rectangular, monophasic, positive current pulses were applied at 10 Hz for a duration of 60 s per stimulation period. DVA was used to observe the stimulation-induced reactions of retinal vessel diameters in response to different provocations. In three DVA measurements, three stimulus conditions were investigated: flicker light stimulation (FLS); electrical stimulation (ES); simultaneous electrical and flicker light stimulation (ES+FLS). Retinal vasodilation caused by these stimuli was compared using paired t-test. The subjects receiving electrical stimulation with 800 µA showed significantly increased retinal vasodilation for ES+FLS compared to FLS (p < 0.05). No significant differences in retinal vessel reactions were found between ES+FLS and FLS in the 400 µA and 1200 µA groups. No retinal vasodilation was observed for ES for all investigated current intensities. The results indicate that positive pulsed electrical stimulation of an adequate intensity enhances the flicker light-induced retinal vasodilation.